"We were thinking too much like adults": Examining the development of teachers' critical and collaborative reflection in lesson study discussions. (May 2022) - Kager, Klara; Jurczok, Anne; Bolli, Swantje; Vock, Miriam
Abstract: This mixed-method study addresses the need for a clear conceptualization of the professional reflection element of Lesson Study (LS), a popular collaborative approach to the professional development of teachers. Grounding and re-framing LS's post-lesson discussion in a theoretical framework of critical and collaborative reflection, we analyze the transcripts of four LS groups at German primary schools, focusing on depth of reflection and teachers' trajectories through their reflective practice. The findings show that LS groups differed significantly in the depth and the trajectories of their reflection processes. We consider implications for post-lesson discussions and critical reflection as a LS core skill. Highlights: We present nuanced visualizations of the micro-diachronic development of teachers' reflective practices. We show that lesson study groups differed significantly in their reflective practices. We identify challenges at different stages of the critical and collaborative reflection process. We propose that rethinking the post-lesson discussion in reflective stages can support its development. We identify reflection as a lesson study core skill that needs to be clearly defined, practiced, and routinized.